Resilience: Distinct Construct or Conglomerate of Existing Traits?. Issue 2 (4th July 2016) - Fogarty, Gerard J.; Perera, Harsha N.
Abstract : Since its inception in mainstream scientific psychology, resilience has emerged as a popular, yet controversial, construct. As evidenced in the target article, this controversy can be attributed, at least in part, to current conceptual and methodological difficulties hampering understanding of the construct. Chief among these concerns is the discriminant validity of resilience with respect to conceptually similar individual differences constructs, such as hardiness, mental toughness, adaptability, and even the five-factor personality dimensions. Advances in research on resilience, and ultimately the utility of the construct in applied settings, hinge on its distinction from related concepts.